Low-cost, 4-system, precise GNSS positioning: A GPS, Galileo, BDS and QZSS ionosphere-weighted RTK analysis - Odolinski, R.; Teunissen, Peter (IOP Publishing Ltd, 2017)
With the combination of emerging GNSSs, single-frequency (SF) precise RTK positioning becomes possible. In this contribution we evaluate such low-cost ublox receiver and antenna performance when combining real data of four CDMA systems, namely L1 GPS, E1 Galileo, L1 QZSS, and B1 BDS. Comparisons are made to more expensive dual-frequency (DF) GPS receivers and antennas. The formal and empirical ambiguity success rates and positioning precisions will first be evaluated while making use of L1+E1, so as to investigate whether instantaneous SF RTK is possible without the need of B1 BDS or L1 QZSS. This is followed by an analysis of the SF 4-system model performance when the residual ionosphere can be ignored and modeled as a function of the baseline length, respectively. The analyses are conducted for a location in Dunedin, New Zealand, and compared to Perth, Australia with the better visibility of BDS and QZSS. The results indicate that successful instantaneous and precise RTK positioning is feasible while using L1 GPS and E1 Galileo data, and that the SF 4-system model is competitive to DF GPS even when residual ionospheric delays are present. We finally demonstrate that when the impact from the ionosphere increases and more than one epoch is needed for successful ambiguity resolution, the SF 4-system model performance can still remain competitive with the DF GPS receivers. This is particularly true in Perth with more satellites and when higher than customary elevation cut-off angles need to be used to avoid low-elevation multipath.